Comparative feeding rates of native and invasive ascidians. (October 2018) - Hoxha, Tedi; Crookes, Steve; Lejeusne, Christophe; Dick, Jaimie T.A.; Chang, Xuexiu; Bouchemousse, Sarah; Cuthbert, Ross N.; MacIsaac, Hugh J.
Abstract: Ascidians have a recent history of species introductions globally, often with strong ecological impacts. Comparisons of per capita effects of invaders and comparable natives are useful to assess such impacts. Here, we explore ingestion rates (IR) and clearance rates (CR) of Ciona intestinalis and Ciona robusta, co-occurring native and non-native ascidians, respectively, from Brittany, France. IR was positively related to food concentration, with the invader responding more strongly to increasing food concentration. CR also differed by species, with the invader demonstrating higher values. C . robusta exhibited a higher functional response (Type I) than did C . intestinalis (Type II). Relative impact measured using seasonal abundance and IR revealed that C . robusta has a much greater impact than C . intestinalis at all food concentrations tested, though the former has a constrained distribution which limits its regional impact. Nevertheless, when abundant, we expect C . robusta to exert a greater impact on algal foods. Highlights: Native and invasive ascidians were collected from the coast of Brittany, France. Invasive C . robusta exhibited greater ingestion rates than native C . intestinalis . Clearance rates of the invader also significantly exceeded those of the native. Invader exhibited a higher functional response (type I) than the native (type II). Across all food levels tested, invader relative impact exceeded that of the native species.